The Good Little Wolf - Benjamin, A. H.; Aspinall, Sarah, 1981- (London : Bloomsbury Education, 2020)
Little Wolf doesn't want to be like the bad wolves in his storybooks. So off he trots into the woods where he tries to be good. But every time Little Wolf helps, everyone gets angry! Will Little Wolf ever be a hero? And will anyone ever write a story about a good little wolf?
First published: Great Britain: A&C Black, 2010
"Book band: Gold" -- Back cover
Junior primary school age.
Keywords: Wolves -- Juvenile fiction; Helping behavior -- Juvenile fiction; Readers (Primary)